Fault tolerant steer-by-wire systems: An overview. (2019) - Huang, Chao; Naghdy, Fazel; Du, Haiping; Huang, Hailong
Abstract: Steer-by-Wire (SbW) is considered to be the most significant innovation among X-by-Wire technologies that will revolutionise the automotive industry. A SbW system comprises of electronic control units, steering assist motors, and sensors that can potentially replace mechanical steering column linkages in a car. Among many issues that should be resolved before the commercialisation of SbW systems, maintaining reliability and fault-tolerance in such systems are two of the most pressing issues. There are many studies reported in the literature on fault detection and isolation (FDI), but fault diagnosis and fault tolerance in SbW systems has not received extensive attention. In this paper, an overview of fault diagnosis approaches with various forms of redundancy for SbW is presented. The existing approaches to fault tolerant control are considered and classified according to different criteria, such as design methodologies and applications. In addition, a comparison of different approaches is briefly carried out to provide an overall picture of historical, current, and future developments in this fault tolerant control for SbW systems.